The CXXC Motifs Are Essential for the Function of BosR in Borrelia burgdorferi - Mason, Charlotte; Liu, Xiaoyan; Prabhudeva, Spoorthy; Ouyang, Zhiming (Frontiers in Cellular and Infection Microbiology, 2019)
BosR, a Fur family member, is essential for the pathogenesis of the Lyme disease pathogen, Borrelia burgdorferi. Unlike typical Fur proteins in which DNA binding represses gene expression, binding of BosR to the rpoS promoter directly activates rpoS transcription in B. burgdorferi. However, virtually nothing is known concerning potential structural features and amino acid residues of BosR that are important for protein function and virulence regulation in B. burgdorferi. Particularly, it remains unknown what structural motifs or residues of BosR coordinate Zn, although previous analyses have indicated that the function of BosR may depend on Zn. To address these information gaps, we herein introduced mutations into four conserved cysteine residues in two putative CXXC motifs of BosR. Our data showed that the ability of BosR to bind Zn was dramatically reduced when the CXXC motifs were mutated. Moreover, we found that the two CXXC motifs contributed to the ability of BosR to form dimers. By using a trans-complementation genetic approach, we additionally demonstrated that both CXXC motifs of BosR were essential for in vivo gene expression regulation. Mutation of any of the four cysteines abolished the transcriptional activation of rpoS. In contrast to wild type BosR, each mutant protein was incapable of binding the rpoS promoter in electrophoretic mobility shift assays. The combined data strongly support that the two CXXC motifs and four cysteines constitute the structural site essential for Zn-coordination, protein dimerization, and the unique regulatory activity of BosR.